A via Vico: ética e mitologia na filosofia de Giambattista Vico - Gonçalves, Celso Eduardo Mendes (2017)
After situating Vico in the Naples of his time and in relation to the questions of modern rationality, as well as carrying out an exercise of philosophical reflection seeking the understanding of the worldview of Vico, this piece of work aims at making explicit the ethic that underlies his work as an ethic of teleological character which privileges the practical life, evidencing a concern for what man can and should do of himself, notwithstanding the guardianship of a divine providence in a cyclical history. However, within the advent of the "age of men," it is verified a process of unfoldment of the human nature in which the development of the individual starts to dictate the development of the community; at the same time, the predominance of abstract rationality dissociated from other human faculties – such as imagination – leads to a preponderant literality in the interpretation of mythology, which pervades the doctrines of religions, moving man away from piety, with the consequent loss of both social cohesion and the human sense of the world. Hence, man decays in the age of the gods, submitting himself to heteronomy in the face of the eternal ideal history. It is identified with the present thesis, therefore, the "master key" indicated by the Napolitan himself with the imagination that underlies poetic wisdom, the application of this interpretative key of the method of his work – the new critical art – is extended to the solution of the pretended paradox between the autonomy and the aimed happiness by a teleological ethic and the cyclical repetition of the eternal ideal history